LSN2424100: a novel, potent orexin-2 receptor antagonist with selectivity over orexin-1 receptors and activity in an animal model predictive of antidepressant-like efficacy - Fitch, Thomas E.; Benvenga, Mark J.; Jesudason, Cynthia D.; Zink, Charity; Vandergriff, Amy B.; Menezes, Michelle; Schober, Douglas A.; Rorick-Kehn, Linda M. (Frontiers in Neuroscience, 2014)
We describe a novel, potent and selective orexin-2 (OX2)/hypocretin-2 receptor antagonist with in vivo activity in an animal model predictive of antidepressant-like efficacy. N-biphenyl-2-yl-4-fluoro-N-(1H-imidazol-2-ylmethyl)benzenesulfonamide HCl (LSN2424100) binds with high affinity to recombinant human OX2 receptors (Ki = 4.5 nM), and selectivity over OX1 receptors (Ki = 393 nM). LSN2424100 inhibited OXA-stimulated intracellular calcium release in HEK293 cells expressing human and rat OX2 receptors (Kb = 0.44 and 0.83 nM, respectively) preferentially over cells expressing human and rat OX1 (Kb = 90 and 175 nM, respectively). LSN2424100 exhibits good exposure in Sprague-Dawley rats after IP, but not PO, administration of a 30 mg/kg dose (AUC0-6h = 1300 and 269 ng*hr/mL, respectively). After IP administration in rats and mice, LSN2424100 produces dose-dependent antidepressant-like activity in the delayed-reinforcement of low rate (DRL) assay, a model predictive of antidepressant-like efficacy. Efficacy in the DRL model was lost in mice lacking OX2, but not OX1 receptors, confirming OX2-specific activity. Importantly, antidepressant-like efficacy of the tricyclic antidepressant, imipramine, was maintained in both OX1 and OX2 receptor knock-out mice. In conclusion, the novel OX2 receptor antagonist, LSN2424100, is a valuable tool compound that can be used to explore the role of OX2 receptor-mediated signaling in mood disorders.